Banking law and practice in Nigeria : machinery for control of banks and banking business - Oche, Patrick Ndubuisi (Jos, Nigeria: Heirs Great Commision, 2004)
The book examines the legal machinery for the control of banks and the banking in Nigeria. The book also discussed legislations like the BOFIA Act, NDIC and CBN acts and how they have been implemented in Nigeria.
Includes Index
lje 03/08/13, ijb 03/04/2019
Loans
Keywords: Banking Law; Banks and banking